2010
DOI: 10.3382/ps.2009-00141
|View full text |Cite
|
Sign up to set email alerts
|

Flexible alternatives to the Gompertz equation for describing growth with age in turkey hens

Abstract: A total of 49 profiles of growing turkey hens from commercial flocks were used in this study. Three flexible growth functions (von Bertalanffy, Richards, and Morgan) were evaluated with regard to their ability to describe the relationship between BW and age and were compared with the Gompertz equation with its fixed point of inflection, which might result in its overestimation. For each function, 4 ways of analysis were implemented. A basic model was fitted first, followed by implementation of a first-order au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 17 publications
(17 reference statements)
3
30
0
4
Order By: Relevance
“…In model II, however, the value is very early, the ratio y pi /a is only 0.080. This anticipation in the occurrence of the infl ection point of functions with fl exibility in its location is reported by Porter et al (2010). The asymptotic deceleration points, pda, were nearly the same for the three functions and models I and III ( 41 months, three races in average).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…In model II, however, the value is very early, the ratio y pi /a is only 0.080. This anticipation in the occurrence of the infl ection point of functions with fl exibility in its location is reported by Porter et al (2010). The asymptotic deceleration points, pda, were nearly the same for the three functions and models I and III ( 41 months, three races in average).…”
Section: Resultssupporting
confidence: 60%
“…However, caution must be taken in adjusting these functions, since measurements in the same individual over time cannot be considered independent, since errors are serially correlated, and this information should be added to the model (Draper and Smith, 1998). Porter et al, 2010), Mendes et al (2009), Mazzini et al (2005), Bergamasco et al (2001) and Calegario et al (2005) have demonstrated the superiority of models with correlation structure in the errors compared to models that do not consider this correlation including. In all comparisons, autoregressive models were superior to models without autocorrelation.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated NLM growth curves and the curve of observed body weights for females and males are shown in Figures 1 and 2, and therefore, the results of the Brody and Richards' curves are not shown, because those models fail to converge, and they were dropped from further analysis. Porter et al (2010) also found that the Richards model fail to converge in Hybrid turkey females.…”
Section: Resultsmentioning
confidence: 92%
“…Growth is the result of an animal gaining weight with time until it reaches maturity (Porter et al, 2010). The knowledge of the growth curve of turkeys is important to develop management practices that could help increase their productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is not appropriate to use linear mathematical functions for describing growth trajectory, a number of nonlinear function has been investigated as alternatives (Sengül and Kiraz, 2005). Thereby, several nonlinear models (NLM) to describe the chicken growth pattern have been proposed (Gompertz, 1825;Grossman et al, 1982;Porter et al, 2010;Tompić et al, 2011).…”
Section: Introductionmentioning
confidence: 99%